PERAN GURU DALAM MENGIMPLEMENTASIKAN NILAI – NILAI PANCASILA - Ahmad Arif Fadilah; anisa, Siti Nailatus Syifa; Zelena Putri Dinata (Sindoro: Cendikia Pendidikan, 2025)
The role of teachers in implementing Pancasila values is essential in shaping students' character aligned with the foundational values of the Indonesian nation. This study aims to analyze teachers' roles in integrating Pancasila values into the teaching and learning process in schools. The research employs a qualitative method with a case study approach in several secondary schools. Data were collected through interviews, observations, and documentation, then analyzed using thematic analysis techniques. The findings reveal that teachers play a strategic role in instilling Pancasila values through character-based teaching, providing concrete examples in daily life, and managing a conducive learning environment. However, the main challenge faced is the lack of specific training for teachers to understand and effectively implement these values. The study concludes that to strengthen the implementation of Pancasila values, continuous support from schools and the government is necessary through training and relevant curriculum development.